Role of colonic epithelial cells in susceptibility and severity of Citrobacter rodentium infection in mice - Gart, Elena Vladimirovna (Kansas State University, 2011)
Acute diarrhea induced by Escherichia coli is an important illness in humans, especially in children under age of two in developing countries. Citrobacter rodentium is used as murine model for E. coli infection in humans because it causes ultrastructural changes in murine colonic epithelium comparable to lesions produced by enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC). Adult mice of many strains develop self-limiting epithelial hyperplasia when infected, whereas adult C3H and FVB mice are highly susceptible to infection and demonstrate mortality rates between 60 and 100% two weeks after infection. These susceptible strains of mice also have higher bacterial translocation to mesenteric lymph nodes. In mice, the cause of death could be hypovolemia due to dehydration that may occur due to an increase in paracellular permeability as well as dysregulation of apical and basolateral ion transporting proteins. C. rodentium virulence factors resemble those of E. coli and are believed to primarily alter tight junctions of colonic epithelial cells. Effectors delivered via the type III secretory system have been associated with actin condensation and pedestal formation. The exact mechanisms of C. rodentium infection, as well as changes that occur in vitro as well as in the intestine of various strains of mice are not completely understood. This study introduced a new in vitro Ptk6 cell line for C. rodentium infection, which can also serve as a model for EPEC in humans. Effect of C. rodentium on colonic epithelial cells of susceptible and resistant mice was determined in in vivo study. C. rodentium attached to Ptk6 colonic epithelial cells, inducing attaching and effacing (A/E) lesions and loss of monolayer integrity, which charachterizes this cell line as a relevant in vitro model of C. rodentium and EPEC infections. Murine studies revealed that C. rodentium induced more severe disease and 100% mortality in juvenile C3H mice whereas Swiss Webster (SW) mice expressed only moderate morbidity. The colonic lesions and changes in barrier function of colonic epithelium were more prominent in C3H mice. This study determined potential targets in the murine colon that play role the establishment and the outcome of the infection, indicating multifactorial nature of C. rodentium-induced diarrhea. This study identified host factors involved in the initiation of C. rodentium-associated diarrhea and the outcome of infection, which can be useful in developing of novel strategies for preventing and treatment of infectious colitis.
Keywords: Enteropathogenic E. coli infection model; C. rodentium susceptibility; C. rodentium pathogenesis; Microbiology (0410); Molecular Biology (0307)